A question of bank notes, cars, and houses! Matchmaking and the Moral Economy of Love in Urban China - Pettier, Jean-Baptiste (Comparative Studies in Society and History, 2022)
Chinese practices of matchmaking have been controversial for over a century. Their continued transformations reveal a complex nexus of sentimental and material dimensions in the marriage-decision process at the heart of the negotiations between families and in their selections of proper candidates. This interplay between personal sentiments, concrete considerations, and the desire for success makes marriage controversial, as love is claimed and proclaimed at the same time. Moral debates around materialism, which have reverberated through the public sphere over the last decade, show how love acts as a tool of social reproduction while it also expresses sincere aspirations for an emotionally satisfying life. In comparative perspective, the complex of romantic love examined here reveals a recent, original synthesis of the tradition of parental arrangement and the political question of the place of love in modernity. The paper elucidates one of the contradictions within Chinese society today: the family remains central, but wider trends of individualization continue to unfold. A multifaceted understanding of love clarifies how it can bind families together while it also discourages others from pursuing romance.
CRIS-Team Scopus Importer:2023-03-21
Keywords: cultural capital.; familism; individualization; marriage; matchmaking; materialism; morality; romantic love; sentiments